POLITENESS PRINCIPLE ANALYSIS IN CARTOON MOVIE ENTITLED STAND BY ME DORAEMON - Eko Mulyono (Premise: Journal of English Education and Applied Linguistics, 2016)
This article examines the use of politeness principle in cartoon movie entitled “Stand By Me Doraemon”. It aims at giving a description on the use of politeness principle in this movie so that this is the source of data as well. The data are collected by note taking technique and then analyzed descriptively. After analyzing the data, the researcher finds the use of politeness principle in the movie script. They are utterances of the use of politeness principle covering the kinds of maxim in politeness principle. The utterances covey the use of tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim, and sympathy maxim. Then, it focused also in politeness scale such as formality scale, hesitancy scale, and equality scale. The finding result showed that there are 25 politeness principle found in cartoon movie “Stand By Me Doraemon”. 1 tact maxim, 3 generosity maxim, 6 approbation maxim, 1 modesty maxim, 2 agreement maxim, 3 sympathy maxim, 2 formality scale, 4 hesitancy scale, and 3 equality scale. Approbation maxim is the maxim of the most numerous in the movie. This is because the characters in this film seek to avoid conflict and create an environment that is comfortable in communication.